FORMAL DEFINITION IN THE INSTITUTE OF LABOUR CONTRACT - Tat’yana Vysheslavova; Svetlana Lukinova (Гуманитарные и юридические исследования)
The article is devoted to the legal analysis of formal certainty level of the norms of the labor contract institution in the labor law. It defines the main features of the evaluative concepts of this institution, their role in ensuring the completeness of the speciication of labor relations that are subject to legal regulation. The importance of an objective-subjective analysis of the application of evaluative concepts of the labor contract institute is analyzed through the analysis of speciic circumstances based on peculiarities of social and labor legal relationships, partial specification of the norms of the labor contract institution in the Labor Code of the Russian Federation, local regulation of labor relations and judicial practice in unifying the formal certainty of the norms of the labour contract institute. The authors come to the conclusion that the formal certainty of the norms of the labour contract institution is mediated by the subjective-individual nature of the employment relationship. A distinctive feature of the evaluative standards of the institution under study is a purposeful, programmed need for formal certainty of diverse legal phenomena that are not included in a speciic list in the Labor Code of the Russian Federation. A laconic statement of the text of the legal norm presupposes the inevitability of the presence of certain evaluative provisions in the regulation of the employment contract. The correct (that is, corresponding to the idea of the legislator) understanding of the evaluative concept of labor law when it is implemented in legal relationships is of great importance, since only it ensures compliance of the normative order with the goals pursued by the legislator in its adoption.